Colorectal cancer survival rates in Makassar, Eastern Indonesia: A retrospective Cohort Study. (February 2022) - Labeda, Ibrahim; Lusikooy, Ronald Erasio; Mappincara,; Dani, Muhammad Iwan; Sampetoding, Samuel; Kusuma, Muhammad Ihwan; Uwuratuw, Julianus Aboyaman; Syarifuddin, Erwin; Arsyad, Arham; Faruk, Muhammad
Abstract: Background: The 5-year overall survival (OS) rate for colorectal cancer (CRC) has been reported as 39%, and the 5-year recurrence-free survival (RFS) rate has been reported as 14%. Various prognostic factors have been associated with differences in survival rates among CRC patients. This study investigated the difference between several prognostic factors and the OS and RFS rates of CRC patients at the Dr. Wahidin Sudirohusodo General Hospital Makassar in Indonesia. Materials and methods: The study group comprised all CRC patients treated at the Division of Digestive Surgery from 2014 to 2016. Prognostic factor data were collected from medical records for 293 patients. The OS and RFS rates were analyzed using the bivariate Kaplan–Meier method and log-rank tests. Results: Log-rank analysis of the association of age, histopathology, stage, definitive surgery, chemotherapy, and radiotherapy with the OS rate showed p -values of 0.031, 0.009, 0.014, 0.000, 0.343, and 0.381, respectively. Log-rank analysis of the association of these prognostic factors with the RFS rate showed p -values of 0.282, 0.006, 0.008, 0.020, 0.002, and 0.000, respectively. Conclusion: There were significant differences in the OS rate according to age, histopathology, stage, and history of definitive surgery. Histopathology, stage, history of definitive surgery, and chemotherapy and radiotherapy were significantly associated with differences in the RFS rate. Highlights: Colorectal cancer is relatively common in Indonesia, and its incidence is slowly increasing. Most Indonesian cases are detected at an advanced stage owing to educational, cultural, social, and economic factors. Histopathology, tumor stage and history of definitive surgery significantly affected recurrence-free survival. Chemotherapy and radiotherapy treatments had significantly different recurrence-free survival rates.